Physical and Motor Development of 5-6 Years Old Children at PAUD Cita Nanda - Husnul Hadi; Muh Isna Nurdin Wibisana (International Journal of Research in Education, 2023)
Early childhood mass is a very important mass for children in the process of increasing physical growth and motor development. Increased physical growth can be done by fulfilling nutrition in children, while motor development can be improved by doing movement activities. Early childhood is accustomed to doing motor movements, both fine motor and gross motor so that the muscles can work properly. This research uses a qualitative descriptive approach. The data in this study were obtained using the observation method of children aged 5-6 years at PAUD Cita Nanda. Data is the result of the achievement of children's physical-motor development. The sample in the study was early childhood in Kindergarten B which amounted to 12 (twelve) children. Based on the results of data from the research subjects, it can be seen that the development of gross motor fine motor children has developed very well, this can be seen from the coordination of the movements performed. In terms of healthy living behavior, children have made it a habit to live clean and healthy. The physical-motor development of children aged 5-6 years has developed very well, this can be seen from the development of gross motor and fine motor of children who are well coordinated, and children's healthy living behavior is as expected, so that children have healthy living behavior habits.